Label-free imaging of blood vessel morphology with capillary resolution using optical microangiography - Reif, Roberto; Wang, Ruikang K. (Quantitative Imaging in Medicine and Surgery, 2012)
Several tissue pathologies are correlated with changes in the blood vessel morphology and microcirculation that supplies the tissue. Optical coherence tomography (OCT) is an imaging technique that enables acquiring non-invasive three-dimensional images of biological structures with micrometer resolution. Optical microangiography (OMAG) is a method of processing OCT data which enables visualizing the three-dimensional blood vessel morphology within biological tissues. OMAG has high spatial resolution which allows visualizing single capillary vessels, and does not require the use of contrast agents. The intrinsic optical signals backscattered by the moving blood cells inside blood vessels are used as the contrast for which OMAG images are based on. In this paper, we discuss a brief review of the OMAG theory, and present some examples of applications for this technique.